2013
DOI: 10.1136/bmjopen-2012-001570
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of evidence on the links between patient experience and clinical safety and effectiveness

Abstract: ObjectiveTo explore evidence on the links between patient experience and clinical safety and effectiveness outcomes.DesignSystematic review.SettingA wide range of settings within primary and secondary care including hospitals and primary care centres.ParticipantsA wide range of demographic groups and age groups.Primary and secondary outcome measuresA broad range of patient safety and clinical effectiveness outcomes including mortality, physical symptoms, length of stay and adherence to treatment.ResultsThis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
1,486
4
27

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,797 publications
(1,547 citation statements)
references
References 73 publications
30
1,486
4
27
Order By: Relevance
“…The ‘ceiling effect’ – participants’ tendencies to rate services more positively in general – is another known confounder, making it difficult to differentiate excellent care from adequate care [23,31]. Participants’ subjectivity – being pleased with services that are not necessarily evidence-based [3234] – poses another confounder for quantitative studies measuring satisfaction. While qualitative studies have emerged as an alternative to study satisfaction, they involve a small group of participants who have been purposefully selected, and findings from such studies rarely can be generalised for programmatic changes, especially so in big countries, like India.…”
Section: Introductionmentioning
confidence: 99%
“…The ‘ceiling effect’ – participants’ tendencies to rate services more positively in general – is another known confounder, making it difficult to differentiate excellent care from adequate care [23,31]. Participants’ subjectivity – being pleased with services that are not necessarily evidence-based [3234] – poses another confounder for quantitative studies measuring satisfaction. While qualitative studies have emerged as an alternative to study satisfaction, they involve a small group of participants who have been purposefully selected, and findings from such studies rarely can be generalised for programmatic changes, especially so in big countries, like India.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been a humanistic shift in healthcare toward understanding how patients experience their care as a means of better supporting their healing. [1][2][3][4] Patient experience data, both quantitative and qualitative, are collected in many ways including a range of data from patient satisfaction and experience which includes stories, anecdotes or narratives spanning the duration of patient care. At the point of care, healthcare providers consistently hear patient's stories and experiences allowing them to informally learn about how patients are experiencing their care.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, Doyle, Lennox, and Bell (2013) found that effective patient-provider communication related to patient experience was shown to positively affect self-rated and objectively measured health outcomes as well as indicate higher levels of adherence to treatment. Research regarding pain management and patient-provider communication reveals seemingly contradictory patient and provider expectations and experiences: a contradiction that confounds the potential for improved pain management outcomes.…”
Section: Discussionmentioning
confidence: 99%